Analysis of the Influence of Learning Methods, Learning Environment, and Motivation on Interest in Learning PJOK (Literature Review Sport Education) - Siska Aprelyani (Siber Nusantara Review, 2025)
Literature Review analysis of the influence of Learning Methods, Learning Environment and Motivation on Learning Interest is a scientific article with the aim of analyzing whether Learning Interest influences learning methods, learning environments and motivation. Qualitative approach method with literature review method to explore and analyze the relationship between learning methods, learning environments, motivation and learning interest. The results of this article are: 1) Learning Methods influence Learning Interest; 2) Learning Environment influences Learning Interest; 3) Motivation influences Learning Interest. Apart from these 2 exogenous variables that influence the endogenous variable Learning Interest, there are many other factors including curriculum, learning style, atmosphere.